Preliminary data on physical well-being of children and adolescents during the SARS-CoV-2 pandemic. (20th October 2021) - Salussolia, A; Montalti, M; Marini, S; Rallo, F; Masini, A; Paternò, M; Agosta, M; Guaraldi, F; Dallolio, L; Gori, D
Abstract: Background: The COVID-19 outbreak has forcibly overshadowed the physical well-being of children and adolescents, of which we will see the consequences in near future. The programs to contain the spread of Sars-CoV-2 resulted in prolonged lockdown periods, discontinuity of educational services and a possible decrease in physical activities (PA) among the youngest. In the local reality of the Metropolitan City of Bologna children and adolescents underwent a radical change in habits and lifestyle, overall predisposing sedentariness and unhealthy behaviors. Our project, "Come te la passi?", aims to acknowledge lifestyle variations (concerning diet, PA, sleep behavior/quality) to design, in second-phase interventions, individualized school-based educational programs. Methods: This ongoing study is being conducted using an on-line anonymous questionnaire targeting parents/guardian of children and adolescents aged 6-17 recruited from 26th to 28th of April in Bologna, a city in Northern Italy. Results: Preliminary data suggested that among adolescents (n = 124) 91.2% used to do PA 2 or more times a week before lockdown, while during lockdown this percentage decreased, reaching 41.1%. In children (n = 38) we observed an even more pronounced difference, with PA decreasing from 89.5% to 26.3%. In children 29% of the participants also reported a weight gain, while 65.8% did not report any variation and only 5.2% reported a weight loss. For the majority of both children's and adolescents' parents (n = 162), the strategies to address the reduction in PA were predominantly having school time dedicated only to PA (53.1%) and being more educated about simple physical exercises (14.5%). Conclusions: Our preliminary findings suggest that the current pandemic had a strong impact on the well-being of children and adolescents; "Come te la passi?" second-phase interventions could be crucial in addressing the youngest' needs, to educate and promote healthier lifestyles through school-based programs. Key messages: Children's and adolescents' lifestyle behaviors were strongly affected by the current pandemic, with physical activity frequency more than halved. "Come te la passi?" objectives are to frame the major critical issues detected and to shape educational school programs based on identified needs.